Mesenteric Ischemia: Diagnosis and Management - Sidhi Laksono; Natasha Anindhia Harsas (Warmadewa University, 2022)
Abstract Mesenteric ischemia is a rare etiology of abdominal pain caused by impaired blood flow to the mesenteric circulation. This condition has acute and chronic variations and is associated with high mortality and morbidity. Early diagnosis is needed to determine management and prevention efforts towards a worse prognosis. The main principles of management of mesenteric ischemia are the restoration of bowel perfusion and resection of the necrotic bowel. This review will discuss the basic materials, diagnosis, and patient management strategies based on the conditions and causes of mesenteric ischemia. Keywords: mesenteric ischemia, necrosis, thrombosis, embolism